Physicochemical stability, antioxidant properties and bioaccessibility of β-carotene in orange oil-in-water beverage emulsions: influence of carrier oil types. Issue 1 (27th November 2017) - Meroni, Erika; Raikos, Vassilios
Abstract : The bioaccessibility of β-carotene in beverage emulsions was enhanced by modifying the lipid composition of the dispersed phase. Abstract : This study investigated the effect of carrier oils (short-chain triglycerides (SCT) vs. long-chain triglycerides (LCT)) on the physical stability, chemical degradation, antioxidant properties and bioaccessibility of β-carotene-loaded orange oil-in-water beverage emulsions. Beverages formulated with 50% LCT (corn oil) were physically more stable compared to the ones with 50% SCT (tributyrin) as indicated by the Turbiscan 32 Stability Indices during chilled storage for 28 days. No chemical degradation of β-carotene was observed during storage regardless of the carrier oil composition. The formation of primary (conjugated dienes) or secondary (thiobarbituric acid reactive substances) oxidation products at the end of the storage period was insignificant. The bioaccessibility of β-carotene was significantly affected ( P < 0.05) by the type of carrier oil and decreased in the following order: 50% LCT + 50% orange oil > 50% SCT + 50% orange oil > 100% orange oil. The high bioaccessibility of β-carotene (30.06%) in the beverages formulated with LCTs was attributed to the enhanced solubilisation capacity of the lipophilic carotenoid in mixed micelles after the in vitro digestion protocol.